EFEKTIVITAS MUHA>SABAH DALAM PENCAPAIAN MAKNA HIDUP PADA SANTRI DI PONPES AL-ITTIFAQIYAH OGAN ILIR SUMSEL - Amaliyah, Rizki (LP2M IAIN Mataram, 2014)
The aim of this research is to reveal the effectiveness of muha>sabah in a process of attaining the meaning of life by the Santris at Madrasa Aliyah, Pondok Pesantren Al â Ittifaqiyah Ogan Ilir regency South Sumatra Province. Respondents are selected based on purposive sampling technique. The respondents are 34 people which are comprised of 17 experiment group, and 17others are control group. Data are gathered through measurement scale; the scale of process attaining the meaning of life which garnered from aspects of life meaning from Viktor Frankl. By as such the data are analyzed through ANOVAs statistics analysis. The figuring is done through applying 20 versions of SPSS for windows. The result of this research shows that the proposed hypothesis; Ha (Î¼ â¥ Î¼) is rejected while zero hypothesis (Hâ) (Î¼ = Î¼) is accepted. It can be justified through seeing (F counting = 3, 13 < F Table = 5,91). Meanwhile normality measurement shows that the variable of process of attaining the meaning of life in experiment group marked by K-SZ we obtained value 0,407 with the significance value 0,996 (p > 0, 05). In control group K- SZ value are 0,501 with significant value 0,963 (p > 0, 05). Based on these values it can be considered that both of these groups are normally distributed. Therefore it can be concluded that muhasabah is ineffective in the process of looking the meaning of life. However, the santris who are given muhasabah will significantly attain the meaning of their life rather than those who does not.